Cell Competition and Its Role in the Regulation of Cell Fitness from Development to Cancer. - Di Gregorio, A.; Bowling, S.; Rodriguez, T.A. (Developmental Cell, 2016)
Cell competition is a cell fitness-sensing mechanism conserved from insects to mammals that eliminates those cells that, although viable, are less fit than their neighbors. An important implication of cell competition is that cellular fitness is not only a cell-intrinsic property but is also determined relative to the fitness of neighboring cells: a cell that is of suboptimal fitness in one context may be "super-fit" in the context of a different cell population. Here we discuss the mechanisms by which cell competition measures and communicates cell fitness levels and the implications of this mechanism for development, regeneration, and tumor progression.